OPPORTUNITIES FOR FORMATION OF PROFESSIONAL CULTURE IN FUTURE PHYSICAL EDUCATION TEACHERS: OPPORTUNITIES FOR FORMATION OF PROFESSIONAL CULTURE IN FUTURE PHYSICAL EDUCATION TEACHERS - xasanov, anvar (Физическое воспитание, спорт и здоровье, 2022)
This article reveals the opportunities for future physical education teachers to form a professional culture. The article also describes the situations that athletes should pay attention to in physical education classes, the integral connection between physical culture and aesthetic education. A look at the history of sports and physical education. The article analyzes the principles that are important for athletes.